UPAYA MEMPERBAIKI PELAKSANAAN ZAKAT FITRI BAGI UMAT MUSLIM INDONESIA (ZISWAF: Jurnal Zakat dan Wakaf, 2016)
AbstractThe standard measure used to pay Zakat al-Fitr is more than one. This means that each region has the size or dose to give. One group is not justified to claim that ukurannyalah the most correct and the other wrong group. This claim is not justified by the science of Usul al-Fiqh. With regards to mandatory zakat Fitr is fed to the poor, the characteristics of the two staple foods (dates and rice) are very different. Dates quite accompanied by water but not the rice. The latter must be cooked first, and must be accompanied by many side dishes, fruit, chili. Due to different characteristics, then the technique to pay zakat Fitr with dates different from the rice. Feeding with groceries date considered sufficient without food or drink companion.